ABO blood group system and occurrence of ischemic stroke - LOTZ,Rafaella Chiodini (2021)
ABSTRACT Background: Ischemic stroke (IS) is a multifactorial disease that presents high rates of morbimortality in Brazil. Several studies proved that there is a link between the ABO blood group system and the occurrence of thrombotic events. Nonetheless, its association with IS is not well established. Objective: For that reason, the purpose hereof was to investigate the relation between the ABO blood groups and the occurrence of IS in a Brazilian cohort of cerebrovascular diseases. Methods: Five hundred and twenty-nine subjects were included over 12 months, from which 275 presented an IS episode and 254 composed the control group. Blood samples were drawn for direct and reverse serotyping. The control and IS groups were compared regarding the traditional risk factors and the distribution of the ABO blood groups. Results: The IS group presented a higher prevalence of systemic arterial hypertension (SAH), diabetes mellitus, smoking habits, family history, cardiopathy, and sedentary lifestyle in comparison with the control group. The AB blood type prevailed among the patients (5.1 vs. 1.6%; p<0.05) and this group had more SAH cases in comparison with the O type group (92.9 vs. 67.3%; p<0.05). Conclusions: Our results suggest that the occurrence of IS is more frequent among patients of the AB blood type.